Hydrothermal Synthesis of Metal–Polyphenol Coordination Crystals and Their Derived Metal/N‐doped Carbon Composites for Oxygen Electrocatalysis. Issue 40 (1st September 2016) - Wei, Jing; Liang, Yan; Hu, Yaoxin; Kong, Biao; Zhang, Jin; Gu, Qinfen; Tong, Yuping; Wang, Xianbiao; Jiang, San Ping; Wang, Huanting
Abstract: Cobalt (or iron)–polyphenol coordination polymers with crystalline frameworks are synthesized for the first time. The crystalline framework is formed by the assembly of metal ions and polyphenol followed by oxidative self‐polymerization of the organic ligands (polyphenol) during hydrothermal treatment in alkaline condition. As a result, such coordination crystals are even partly stable in strong acid (such as 2 m HCl). The metal (Co or Fe)‐natural abundant polyphenol (tannin) coordination crystals are a renewable source for the fabrication of metal/carbon composites as a nonprecious‐metal catalyst, which show high catalytic performance for both oxygen reduction reaction and oxygen evolution reaction. Such excellent performance makes metal–polyphenol coordination crystals an efficient precursor to fabricate low‐cost catalysts for the large‐scale application of fuel cells and metal–air batteries. Abstract : Coordination crystals (see SEM image) obtained from a polyphenol (tannic acid; TA) and cobalt or iron were synthesized by a hydrothermal synthesis route. The crystals are a renewable source for the fabrication of metal/carbon composites as a nonprecious metal catalyst for the oxygen reduction and evolution reactions.